Two Canariella species (Gastropoda: Helicodea: Hygromiidae) endemic to the Northwest Tenerife (Canary Islands) - Ibáñez, Miguel; Siverio, Felipe; Alonso, María R.; Ponte-Lira, Carmen E. (Zootaxa, 2006)
Canariella giustii sp. nov. is described and morphological data for C. pontelirae Hutterer, 1994, previously believed extinct, are added. C. giustii differs from all the other known species of the genus mainly by the broadened penis, with a lateral-proximal epiphallar opening and the extension of the two epiphallar folds in the penial cavity without merging in a penial papilla. Both species are endemic to Teno massif (Tenerife Island).        The range of the living population of C. pontelirae is very small, only of about 0.4 km2, and tourism has significant effect over the entire area. Thus, C. pontelirae is seriously threatened. It is recommended that the species be classified as “Critically Endangered”, that it be included in the Habitats Directive Annex II and IV of the European Union, and to increase the legal protection level of its relic distribution area to the category of "Site of Scientific Interest". Nine other endemic land snail species also live at that site (among them, C. giustii) and they would benefit from this new level of protection.